Expansion of the genomic and functional diversity of global ocean giant viruses - Benjamin Minch; Mohammad Moniruzzaman (npj Viruses)
Abstract Giant viruses (GVs) play crucial roles in the global ocean microbial food web and biogeochemistry. Recent metagenomic advances have uncovered >1800 new GV genomes from the world’s oceans. While this rapid increase in genomic information is impressive, it is nowhere close to the extensive genomic information available for other marine entities—e.g., prokaryotes and their “virome”. We present 230 new high-quality GV genomes (genomes with 4 or more marker genes) and 398 partial genomes from nine global ocean datasets. Notably, we identified numerous GV genomes from the Baltic Sea, offering insights into their phylogenomics, metabolic potential, and environmental drivers in one of the largest brackish water ecosystems. We discovered new GV functions and identified a significant functional divide between the Imitervirales and Algavirales orders. Additionally, we evaluated factors affecting GV abundance through a case study on the Baltic Sea dataset. Our study significantly expands the marine GV genomic and functional diversity, broadening our understanding of their roles in the food web and biogeochemistry.